Thermal transport behavior of polycrystalline graphene : a molecular dynamics study - Wu, P. H. (2014)
The thermal transport behavior of polycrystalline graphene is studied using molecular dynamics simulations, with focus on the effects of grain size, tensile strain, and temperature on the thermal conductivity. All the simulation samples have the same overall dimensions of 30 × 30 nm with average grain sizes ranging from 2.5 to 12.5 nm. It is found that polycrystalline graphene exhibits a significant reduction in thermal conductivity compared to single-crystalline graphene, and the smaller the grain size is, the more the thermal conductivity drops. The thermal conductivity of polycrystalline graphene with average grain size of 2.5 nm is only about 20% of single-crystalline graphene. However, the thermal conductivity of polycrystalline graphene is less sensitive to both the applied strain and temperature than that of single-crystalline graphene. The underlying mechanisms for the differences in thermal behavior are examined and discussed. These findings are important for the thermal management of graphene-based devices.